The Impact of Sustainable Investing: A Multidisciplinary Review - Marti, Emilio; Fuchs, Martin; DesJardine, Mark R.; Slager, Rieneke; Gond, Jean‐Pascal (Journal of Management Studies, 2024)
AbstractWe conduct a multidisciplinary review of how sustainable investing impacts the environment and society. Our review starts from the insight that shareholders can create impact not only through (1) portfolio screening and (2) shareholder engagement (two impact strategies most used by mainstream shareholders) but also through (3) field building (an impact strategy most used by shareholders at the periphery of the financial sector). Based on this framework of three impact strategies, we integrate insights from four disciplines (management, finance, sociology, and ethics/sustainability) to reconstruct how each impact strategy influences corporate sustainability. We identify 15 impact mechanisms through which the impact strategies produce three types of impact: portfolio screening and shareholder engagement mostly create direct impact on companies, while field building creates indirect impact via other shareholders and indirect impact via the institutional context. Our review suggests that shareholder impact emerges gradually as different types of shareholders build on each other's efforts, which we use to outline a research agenda on shareholder impact as a distributed process.